(3HjGf GdMb HVeGf GdUObs - (3CHh GdYHGS GddhcQjs
(3ChdgG (B:s
(3GdMeO ddg ceG Cgdg gPG gh GdLRAGdKGdK ef GdcJGH GdeDda aiGdYdhe GdMcejI hbUOfG ajgG Cf fJcde ai CUhd GdYde GdEdgi s
(3BNQgG (B:s
(3BNQ GdehLhO efg CKfGA LedI aUhd efJNHI ef Yde GdCNdGb JTJed Ydi GcJSGH aVGjd GdfaS GdEfSGfjI CMOGgeG GdeHOC hai GdefJgi hajeG HjfgeG GdMaGb GdQCi s
(3Vef eLehY , JQJjHgG (B: (3GdKGdKs
(3GfXQ GdeNWhW Qbe (B53 (3GNJUQ ef cJH GdQFjS GHf SjfG hGdaGQGHis
(3HgG fXGe GdJYbjHIs
(3JHUQGJ GdCUd (B:s
(3GdfSNI eHJhQI GdBNQ s
(3GdfSNI HgG JdhjK s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdadSaI hGdefWbs